Knowledge, perception, and acceptance toward the booster dose of COVID-19 vaccine among patients visiting dental clinics in Aseer region of KSA - Shahabe Saquib Abullais; Suraj Arora; Meelaf Al Shahrani; Abdul Ahad Khan; Waleed Al Shahrani; Syed Esam Mahmood; Saad Al Qahtani; Mohammed Maqbool; Ahmad Saib Jameel; Priyanka Saluja (Human Vaccines & Immunotherapeutics, 2022)
Scientists have emerged with innovative research on non-human primates showing that the booster dose of the COVID-19 vaccine increases neutralizing antibody levels against all variants. The current cross-sectional survey was designed to evaluate the knowledge, perception, and acceptance of the booster dose of the COVID-19 vaccine among the patients visiting the various dental clinics in Aseer region, Kingdom of Saudi Arabia. A total of 609 dental patients were selected from various dental clinics by a simple random probability sampling method. The questionnaire was designed in multiple languages and categorized as demographic information, knowledge, perception, and acceptance of participants to a booster dose. An anonymous, self-administered, closed-ended online, and paper-based questionnaire was used to assess the above parameters. In the current survey, the majority of the participants were Saudis (80.8%) with an age mean of 37.7 ± 8.7 years. About 68.6% (418 out of 609) of participants had poor knowledge about the booster dose. Significant differences in the levels of knowledge were found in relation to gender, area of residency, education, nationality, and occupation. The distribution of level of perception of booster dose differs significantly among participants of different marital statuses and nationalities. Hesitation to booster was reported more in the rural than in the urban population. Despite a low level of knowledge, a higher level of good perception and acceptance of booster doses were reported among the studied population.